Value and prediction of critical content-level to assess the nitrogen status of the potato - Coelho, Fabrício (2012)
Regardless of the nitrogen (N) content used, the existence of values, accepted as a critical concentration, is necessary for use as a reference standard. The objective was to establish critical levels of the SPAD index, Hue angle, concentration of total N, and fourth-leaf dry matter of the potato plant, by two methods, and to use such critical levels for the prediction of the N-status of the plant, based on the relative yield. The experiments were conducted on crops from the winter and rainy seasons. The treatments consisted of five dosages of N, applied in the form of urea when planting (0, 50, 100, 200 and 300 kg ha-1 of N). The design was of randomized blocks with four replications. The potato cultivar used was Agata. At 21 days after emergence (DAE) the SPAD index, concentration of total N, Hue angle and dry weight of the fourth leaf from the apex of the plant (MSQF), were all determined. To calculate the critical level, the Cate-Nelson graphical procedure and a mathematical procedure were used. The prediction errors of the diagnosis of the N-status determined from the critical levels were estimated using the Cate-Nelson graphical method, by quantifying the percentage of observations which were located in negative quadrants. There was an apparent discrepancy in the critical-level values of N when using the two calculation procedures. The critical levels determined at 21 DAE are suitable for making relatively accurate assessments of N sufficiency at an early stage of evaluation.